DESIGN AND APPLICABILITY OF A NEW ARCHITECTURE OF A DOUBLE SCARA ROBOT - Iosif TEMPEA; Adriana LIVADARIU; Alexandra-Elza MICU (Fiabilitate şi Durabilitate)
SCARA robot mechanisms can be divided into two categories namely : mechanisms consisting of open kinematic chains and mechanisms consisting of closed kinematic chains. The second category includes Double SCARA robot, which comprises a five bar mechanism. The paper will propose several variants of mechanisms for Double SCARA robots, modeled by CATIA software